АЙДАР-АРНАСОЙ КЎЛЛАР ТИЗИМИДА ТУРИЗМНИ РИВОЖЛАНТИРИШ ИМКОНИЯТЛАРИ - Усманов, М.Р.; Абдираманов, Ж.Б. (SCIENCE and SOCIETY, 2023)
This article is presented on the formation of the Aydaro-Arnasoy lake system, the organization of tourism in the Aydaro-Arnasoy lake system, ecotourism, and the development of tourism routes.